Securitising transnational crime: the political drivers of police cooperation between Australia and Indonesia - McKenzie, Michael (Policing and society, 2019)
Why are national police forces increasingly seeking to work together to combat crime? Scholars agree that these cooperative efforts are not simply a response to a growth in transnational crime but debate remains about the broader social and political dynamics involved. Through a case study of the policing relationship between Australia and Indonesia, this article argues that the increasing tendency of governments to frame transnational crime as a security issue is a central driver of international police cooperation. To illustrate this ‘securitising’ discourse, the article discusses various ‘wars on crime’ prosecuted by the two countries since the 1970s.